Targeted gut microbiome therapy: Applications and prospects of probiotics, fecal microbiota transplantation and natural products in the management of type 2 diabetes - Luqi Qin; Bei Fan; Yixia Zhou; Jiahuan Zheng; Rao Diao; Fengzhong Wang; Jiameng Liu (Pharmacological Research)
Type 2 diabetes mellitus (T2DM) is considered as one of the most pressing public health challenges worldwide. Studies have shown significant differences in the gut microbiota between healthy individuals and T2DM patients, suggesting that gut microorganisms may play a key role in the onset and progression of T2DM. This review systematically summarizes the relationship between gut microbiota and T2DM, and explores the mechanisms through which gut microorganisms may alleviate T2DM. Additionally, it evaluates the potential of probiotics, fecal microbiota transplantation (FMT)/virome transplantation (FVT), and natural products in modulating gut microbiota to treat T2DM. Although existing studies have suggested that these interventions may delay or even halt the progression of T2DM, most research remained limited to animal models and observational clinical studies, with a lack of high-quality clinical data. This has led to an imbalance between theoretical research and clinical application. Although some studies have explored the regulatory role of the gut virome on the gut microbiota, research in this area remains in its early stages. Based on these current studies, future research should be focused on large-scale, long-term clinical studies and further investigation on the potential role of the gut virome in T2DM. In conclusion, this review aims to summarize the current evidence and explore the applications of gut microbiota in T2DM treatment, as well as providing recommendations for further investigation in this field.